Controlled single and repeated impact testing for material plastic behaviour characterisation under high strain rates. (9th August 2021) - Breumier, Simon; Trudeau‐Lalonde, Francis; Lafrance, Thierry; Robert, Etienne; Villani, Aurélien; Kermouche, Guillaume; Lévesque, Martin
Abstract: Instrumented single‐shot experiments provide crucial information of a material's response to impact events that can be used in shot‐peening modelling. However, no authors successfully used such test for constitutive model identification and validation as existing test rig generally cannot provide an accurate determination of the shot trajectory in three dimensions over a wide velocity range. In this work, a shot‐peening test rig that can propel single shot under the process conditions with a high aiming accuracy is presented. The test rig propels industrial shot by sudden pressurised gas release. A methodology to recover the propelled shot three‐dimensional trajectory within a 200‐μm accuracy using two high‐frequency cameras is developed in an open‐source in‐house code. The test rig can propel 0.5‐, 1.19‐ and 2.5‐mm‐diameter shot at velocity ranging from 0.8 to 143 m s −1 and can send several shots at the same position when using the largest shot diameter. Two potential applications of the set‐up are presented for (i) coefficient of restitution measurement with different shooting angles and velocities and (ii) crystal plasticity finite element model validation using the impact dent topology, the shot displacement curve and the crystal misorientation field under the dent.